Аналіз розвитку мереж у зв'язку із застосуванням когнітивних технологій - Коляденко, Ю. Ю.; Дробяз, М. О.; Майба, М. А.; Шлома, О. К. (ХНУРЕ, 2022)
The use of modern wireless transmission technologies is determined by the licensing policy for the use of radio frequency spectrum, where national communications administrations allocate radio frequency spectrum users the right to use frequencies within the framework of current norms and rules for the allocation of bands between radio services of Ukraine. The form of permits for the use of radio frequency channels provides for frequency allocation on a long-term basis. The paper analyzes the development of networks in connection with the use of cognitive technologies.
Keywords: безпроводові мережі; РЧС; когнітивні технології